Using spatial, economic, and ecological opinion data to inform gray wolf conservation. (21st September 2016) - Berry, Meredith S.; Nickerson, Norma P.; Metcalf, Elizabeth Covelli
ABSTRACT: Public opinion can be an influential factor in wildlife management decisions. Evaluating public opinions can help legitimize, or delegitimize, management and facilitate long‐term conservation goals. This is especially true for the controversial issues surrounding the management of predators. We surveyed Montana, USA, residents during summer of 2013 to measure public opinion regarding economic and ecological impacts of the gray wolf ( Canis lupus ), and current management of this species. Although opinions were polarized in some areas, a greater percentage of Montanans think that wolves negatively affect the economy, but impact tourism (which contributes to the economy) positively. These differences may reflect the belief that rancher economic losses from wolf predation of cattle is greater than overall tourism gains related to wolves (e.g., wolf‐watching), in addition to the perception of wolves negatively affecting big game (e.g., elk [ Cervus canadensis ]). Results also show that a slightly greater percentage of Montanans feel that wolves positively rather than negatively affect the ecosystem. Regarding specific practices, more Montanans than not have a positive opinion of maintaining wolves on the landscape and also support hunting of wolves. More Montanans hold negative rather than positive opinions, however, regarding wolf trapping. This result was most evident in western Montana as assessed by a spatial distribution of opinions by county and has implications for current wolf management and nontarget species. Results of ordinal regression analyses revealed that big game hunters, males, and those who held negative opinions of the effect of wolves on the Montana ecosystem and economy were significantly more likely to support both hunting and trapping practices. Living in western Montana predicted positive opinions of hunting, but alternatively, negative opinions of trapping. These results provide an understanding of public opinion of wolf management by county as well as statistical inferences that can be useful for informing more regionally oriented management practices. © 2016 The Wildlife Society. Abstract : Montana resident opinions regarding wolf conservation and management practices showed that more Montanans than not believe wolves positively impact the ecosystem and tourism, but negatively impact the economy. In addition, more Montanans than not have negative opinions of trapping, but positive opinions of hunting, a result that is particularly evident in western Montana as evidenced by a spatial distribution analysis.